2021
DOI: 10.1186/s13098-021-00709-5
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC2 restrains high glucose-induced proliferation, inflammation and fibrosis in human glomerular mesangial cells through mediating miR-135a-5p/TIMP3 axis and JNK signaling

Abstract: Background Diabetic nephropathy (DN) is a common complication of diabetes. Long non-coding RNA (lncRNA) cancer susceptibility candidate 2 (CASC2) is reported to exert a protective role in DN by a previous study. The working mechanism underlying the protective role of CASC2 in DN progression was further explored in this study. Methods The expression of CASC2 and microRNA-135a-5p (miR-135a-5p) was determined by real-time quantitative polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…The uncontrolled proliferation of renal mesangial cells is an important pathological feature of human renal diseases, including diabetic nephropathy (Cove‐Smith & Hendry, 2008). In our study, we found that the proliferation of HRMCs was promoted under HG condition, which was consistent with the results of previous studies (Wang et al, 2022; Zhu et al, 2021). Hyperglycemia‐induced oxidative stress has important roles in pathogenesis of diabetic nephropathy (Rosas‐Martínez et al, 2021; Vodosek Hojs et al, 2020), and HG could result in oxidative stress in renal mesangial cells (Wan et al, 2022; Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The uncontrolled proliferation of renal mesangial cells is an important pathological feature of human renal diseases, including diabetic nephropathy (Cove‐Smith & Hendry, 2008). In our study, we found that the proliferation of HRMCs was promoted under HG condition, which was consistent with the results of previous studies (Wang et al, 2022; Zhu et al, 2021). Hyperglycemia‐induced oxidative stress has important roles in pathogenesis of diabetic nephropathy (Rosas‐Martínez et al, 2021; Vodosek Hojs et al, 2020), and HG could result in oxidative stress in renal mesangial cells (Wan et al, 2022; Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…It is generally accepted that lncRNAs exert their biological roles by acting as miRNA sponges and forming an lncRNA-miRNA-mRNA axis. 29 SNHG6 sponges miR-944 and promotes KPNA5 expression, thereby weakening gemcitabine resistance in pancreatic cancer. 30 In addition, SNHG6 enhances hyperoxia-induced lung cell injury via miR-335-KLF5.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, miR‐135a‐5p was mainly discussed in the context of functional disability in cancer, neurogenic diseases and cardiovascular diseases 17–19 . However, miR‐135a‐5p may also contribute to inflammation, adipogenesis and glucose metabolism, implying its potential for further mechanical exploration of GDM 20–22 . It is still unknown how miR‐135a‐5p affects the development of GDM.…”
Section: Discussionmentioning
confidence: 99%